Who is Working for Whom? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Jean Kuate, Yaoundé, Cameroon: 'I was looking again at the cartoon published in Spore No 56 of April 1995. A woman who is digging is followed by a long line of all kinds of people. This made me laugh but also cry because it is a sad reflection of...